LIFE SATISFACTION AMONG OLD AGED PEOPLE ATTENDING FAUJI FOUNDATION HOSPITAL - Mehwish Riaz (Army Medical College Rawalpindi, 2021)
Objective: To determine life satisfaction in old age people attending Fauji Foundation Hospital and to assess relationship of socio-demographic variables on life satisfaction of old aged people.